Impact of Baseline and Postprocedural Intravascular Ultrasound Findings on 1-Year Primary Patency After Drug-Coated Balloon Treatment of Femoropopliteal Lesions. (February 2022) - Horie, Kazunori; Tanaka, Akiko; Taguri, Masataka; Inoue, Naoto
Purpose: Drug-coated balloons (DCBs) are commonly used for endovascular treatment of femoropopliteal lesions. Here, we employed intravascular ultrasound (IVUS) to investigate the predictors of restenosis after DCB treatment. Methods: This retrospective and single-center study was performed to examine 1-year primary patency after DCB treatment and to identify the risk factors for restenosis by analyzing clinical characteristics, angiographic findings, and IVUS measurements. We included 111 consecutive patients undergoing DCB treatment for de novo femoropopliteal lesions at our hospital from July 2018 to March 2020. Results: The primary patency rate was found to be 80.0% at 1 year. The Cox proportional hazard multivariate analysis revealed that restenosis was independently associated with chronic total occlusion (CTO; p < 0.001), circumferential calcification (p = 0.023), and smaller postprocedural minimum lumen area (MLA; p = 0.036). Furthermore, receiver operating characteristic curve analysis showed that the cutoff value of postprocedural MLA to prevent restenosis was 12.7 mm 2, with an area under the curve of 0.774 (p< 0.001). The multivariate analysis indicated that patients with a postprocedural MLA below 12.7 mm 2 (n = 44) had a significantly smaller distal reference vessel size (p < 0.001) compared to those with a postprocedural MLA over 12.7 mm 2 (n = 67). Conclusions: Restenosis after DCB treatment was shown to correlate with CTO, circumferential calcification, and postprocedural MLA as evaluated by IVUS. Moreover, smaller vessel sizes might represent a particular challenge to the DCB strategy due to the difficulty of restoring a sufficient postprocedural lumen area by balloon dilatation.